2015
DOI: 10.18632/oncotarget.5977
|View full text |Cite
|
Sign up to set email alerts
|

EpCAM based capture detects and recovers circulating tumor cells from all subtypes of breast cancer except claudin-low

Abstract: PurposeThe potential utility of circulating tumor cells (CTCs) as liquid biopsies is of great interest. We hypothesized that CTC capture using EpCAM based gating is feasible for most breast cancer subtypes.ResultsCancer cells could be recovered from all intrinsic subtypes of breast cancer with IE/FACS, however, claudin-low cell lines showed very low capture rates compared to the four other groups (p = 0.03). IE/FACS detection of CTC mimic cells was time sensitive, emphasizing controlling for pre-analytic varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…The impact of EMT-associated EpCAM downregulation on CTC detection by EpCAM-dependent techniques, such as the CellSearch Ò system, has been repeatedly reported. Although most of BC subtypes can be efficiently captured by EpCAMbased assays (Ring et al, 2015), several EMT-related antigens have been successfully investigated in addition to EpCAMbased immunoselection as an effective way to increase CTC detection (Mostert et al, 2012Onstenk et al, 2015a;Satelli et al, 2015).…”
Section: Ctc and Epithelialemesenchymal Transitionmentioning
confidence: 99%
“…The impact of EMT-associated EpCAM downregulation on CTC detection by EpCAM-dependent techniques, such as the CellSearch Ò system, has been repeatedly reported. Although most of BC subtypes can be efficiently captured by EpCAMbased assays (Ring et al, 2015), several EMT-related antigens have been successfully investigated in addition to EpCAMbased immunoselection as an effective way to increase CTC detection (Mostert et al, 2012Onstenk et al, 2015a;Satelli et al, 2015).…”
Section: Ctc and Epithelialemesenchymal Transitionmentioning
confidence: 99%
“…In fact, relatively high numbers of apoptotic CTCs have been reported in blood samples from peripheral blood, evidencing their fragility. It has been reported that cancer cell numbers in blood samples rapidly decline over a time span of 5 h, revealing that the time from blood draw to cell harvest is critical . Other reports have shown that a significant RNA degradation occurs within a period of 2–4 h .…”
Section: Current Outlook Of Ctcs In Liquid Biopsymentioning
confidence: 99%
“…Anti-EpCAM antibody coating has been demonstrated to have an outstanding cell capture efficiency in both static and dynamic systems. [98][99][100][101] In the case of CTCs, most positive enrichment is grounded on the EpCAM antibodies. For example, He et al proposed a biocompatible and surface roughness controllable nano-film which is composed of TiO 2 nanoparticles for highly efficient CTC capture and in-situ identification by immunocytochemistry ( Fig.…”
Section: Affinity Reactionmentioning
confidence: 99%